Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-106
|View full text |Cite
|
Sign up to set email alerts
|

Re-enacted and spontaneous conversational prosody: How different?

Abstract: Previous work has shown that read and spontaneous monologues differ prosodically both in production and perception. In this paper, we examine whether similar effects can be found between spontaneous and read, or rather acted, dialogues. It is possible that speakers can mimic conversational prosody very well. Alternatively, they might use prosodic resources more than the conversational situation actually requires (overacting). Another possibility is that in acted dialogues, prosody is actually used less as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…In accord with our prosodic expectations, we found evidence that the speakers of the VR test group gave their elevator pitches in a more listener-oriented, dialogue speaking style than the speakers of the control group. Compared to the latter group, the presentations of the VR test group were characterized by a higher F0 level, a larger F0 range, and a slower speaking rate [6,9,12,13,14,15,16]. Moreover, matching the relatively large speaker-listener distance in the VR situation, the VR test group speakers gave their elevator pitches at a higher intensity level [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accord with our prosodic expectations, we found evidence that the speakers of the VR test group gave their elevator pitches in a more listener-oriented, dialogue speaking style than the speakers of the control group. Compared to the latter group, the presentations of the VR test group were characterized by a higher F0 level, a larger F0 range, and a slower speaking rate [6,9,12,13,14,15,16]. Moreover, matching the relatively large speaker-listener distance in the VR situation, the VR test group speakers gave their elevator pitches at a higher intensity level [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Although read speech and spontaneous speech both constitute a spectrum of styles depending on medium, preparation, and the amount of interaction [7,8,9,10,11], there 9th International Conference on Speech Prosody 2018 13-16 June 2018, Poznań, Poland are recurring acoustic features associated with the differences between spontaneous and read speech. Compared to readspeech monologues, spontaneous speech dialogues show, for example, a lower speaking rate [5,12,13,14], a higher F0 mean [9] and a larger F0 variability [6,9,12,15,16].…”
Section: Prosodic Parameters Related To (Q1) and (Q2)mentioning
confidence: 99%
“…Yet other studies present differences between read and spontaneous dialogues (e.g., [9]), which we can then relate to contrastive analyses of read and spontaneous monologues [10,11,12]. The overall results patterns are not fully consistent across studies [13]. However, what crystallizes across studies is that, compared to spoken monologues, dialogue speech is characterized by a slower speaking rate as well as by a higher level and a larger range of the fundamental frequency or f0 (i.e.…”
Section: Introductionmentioning
confidence: 61%
“…the lowest frequency of the produced speech signal that provides the acoustic basis for listeners perception of pitch and, thus, speech melody, [14]). Studies by [15] and [16], amongst others, also found that dialogues show significantly more silent pauses and hence shorter prosodic phrase durations than monologues ( [17], see also [13]), or faked dialogues (without any addressee).…”
Section: Introductionmentioning
confidence: 97%
“…We set the floor and ceiling frequency values to 75Hz and 400Hz respectively. Utilizing an approach implemented in [16] we filtered out frequency values that were outside 1.5 times the interquantile range for the speaker. The extracted intonational features include F0mean, F0std, and F0range and are plotted in Figure 3.…”
Section: Intonationmentioning
confidence: 99%